Selección de líneas de maíz (Zea mays L.) con resistencia al virus del mosaico de la caña de azúcar (SCMV) - Salazar Erazo, Sandra Milena; León, C. de (2001)
Recent changes in the production systems of maize (Zea mays L.), including staggered and continue growing of the cultivation in Colombia, have increased the incidence of some diseases, among these stands out the sugar cane mosaic virus (SCMV). Several studies have demonstrated that the incidence of this disease can affect maize yields considerably. One of the most economic ways of solving the problem is using genetic resistance to the disease. The present research had as main objective to select resistant S1 lines to the SCMV from acid soil tolerant yellow and white maize base populations. In the cycle 1999A, 282, 155, 287 and 254 S1 lines were evaluated, derived from the acid soil tolerant maize populations SA3, SA4 (with yellow endosperm), SA6 and SA7 (with white endosperm). Seven-day old seedlings grown under screen house conditions, were mechanically was inoculated using leaf tissue from plants with characteristic symptoms of the virus. The infective tissue was ground in 10 - 15 ml phosphate buffer solution (0.1 M KPO4, pH 7.5) and inoculated rubbing in the leaves using carborundum as abrasive. The lines were evaluated 7 days after inoculation using the percentage of infected seedlings with symptoms of the disease. The results indicated that for the range of the 0 - 10 % infection, population SA7 showed the highest frequency of resistant lines to SCMV (76.4%), while populations SA4, SA3 and SA6 presented frequencies of 57.5, 49.5 and 27.5%, respectively. After evaluation 140, 89, 80, and 194 S1 lines were selected from population SA3, SA4, SA6 and SA7, respectively, as resistant to the virus. The obtained information is being utilized to increase the resistance levels to SCMV of the base maize populations and in the development of resistant synthetics and hybrids resistant to SCMV and tolerant to acid soil.